BUKU SAKU MATEMATIKA BERBASIS BUDAYA DAYAK MAYAN DENGAN PENDEKATAN RME UNTUK MELATIH BERPIKIR KRITIS - Rismawati, Melinda; Andri, Andri (Universitas Muhammadiyah Ponorogo, 2024)
The background of this study is the students' low critical Mathematical thinking skills at SMP Negeri 3 Selimbau. This pocketbook media can be combined with Realistic Mathematics Education, which is based on Dayak Mayan culture, as a learning resource. This research aims to determine the validity, practicality, effectiveness, and students' responses to the Dayak Mayan culture-based Mathematics pocketbook. This is development research (RD) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data collection techniques use validation sheets to measure validity, readability questionnaire sheets to measure the level of practicality, test questions to measure effectiveness, and response questionnaires to determine students' responses to the pocketbook that has been developed. The results of the research show that the level of validity of the pocketbook is in the very valid category with an average score of 90.72%, the level of practicality of the pocketbook is in the convenient category with an average score of 94.04%, the level of effectiveness of the pocketbook is in the very good category with an average score obtained by students of 98.51. Student responses to the pocketbook were very good, with questionnaire response results of 88.88%.